Evaluating the effects of platelet-rich plasmas plus dehydroepiandrosterone and dehydroepiandrosterone alone in infertile women with diminished ovarian reserve - Akter, Sohely; Anwary, Shaheen A.; Nessa, Amitun; Sultana, Rebeka; Rolly, Suraiya J.; Altarique, Mostafa M.; Alamgir, Chowdhury F.; Darmini, Maliha; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Diminished ovarian reserve (DOR) is a significant cause of female infertility, often associated with poor response to ovarian stimulation during assisted reproductive techniques. This study aimed to evaluate the effects of a combination therapy using platelet-rich plasma (PRP) and dehydroepiandrosterone (DHEA) compared to DHEA alone in infertile women with DOR. Methods: This Quasi-experimental study was conducted in the Department of Reproductive Endocrinology and Infertility, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from July 2022 to June 2023. In this study, we included 36 women aged 20 to 39 years diagnosed with diminished ovarian reserve (DOR) attending the outpatient Department of Reproductive Endocrinology and Infertility at BSMMU. Participants were assigned to two treatment groups: group A received DHEA plus PRP, and group B received only DHEA. Results: The mean age in group A was 31.5±5.5 years (range: 25–39), and in group B, it was 31.4±5.2 years (range: 25–39). Baseline characteristics, including age, body mass index (BMI), infertility duration, and hormonal levels, were similar between the groups. Over the 3-month follow-up, both groups showed improvements in ovarian reserve markers. Group A demonstrated slightly greater improvements in AMH (0.36±0.2 ng/ml versus 0.30±0.1 ng/ml), AFC (1.2±1.4 versus 0.82±1.5), and a greater reduction in FSH (-3.1±1.9 mIU/ml versus -2.82±1.7 mIU/ml) compared to group B. However, these differences were not statistically significant. Conclusions: This study showed that both DHEA alone and in combination with PRP resulted in improved ovarian reserve markers in women with DOR. Although the combination therapy of PRP and DHEA showed slightly better outcomes compared to DHEA alone, the differences were not significant.